2023
DOI: 10.1038/s41586-022-05512-4
|View full text |Cite
|
Sign up to set email alerts
|

Financial incentives for vaccination do not have negative unintended consequences

Abstract: Financial incentives to encourage healthy and prosocial behaviours often trigger initial behavioural change1–11, but a large academic literature warns against using them12–16. Critics warn that financial incentives can crowd out prosocial motivations and reduce perceived safety and trust, thereby reducing healthy behaviours when no payments are offered and eroding morals more generally17–24. Here we report findings from a large-scale, pre-registered study in Sweden that causally measures the unintended consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…We confidently conclude that there is no evidence supporting our pre-registered hypothesis that the cash incentives treatments would depress the vaccination intentions and behaviors of those residing in cash-treated villages who did not receive cash for vaccines. This is consistent with a recent Swedish random control trial that has found no evidence of spillover effect of COVID-19 financial incentives on future vaccination uptake (Schneider et al, 2023). More generally it is consistent with a recent large-scale cash-transfer trial in rural Africa that also find no evidence of negative spill-over to proximate non-recipients of these cash transfers (Egger et al, 2022).…”
Section: Figure 1: Flow Chart Of Ghana Financial Incentives Trialsupporting
confidence: 88%
See 1 more Smart Citation
“…We confidently conclude that there is no evidence supporting our pre-registered hypothesis that the cash incentives treatments would depress the vaccination intentions and behaviors of those residing in cash-treated villages who did not receive cash for vaccines. This is consistent with a recent Swedish random control trial that has found no evidence of spillover effect of COVID-19 financial incentives on future vaccination uptake (Schneider et al, 2023). More generally it is consistent with a recent large-scale cash-transfer trial in rural Africa that also find no evidence of negative spill-over to proximate non-recipients of these cash transfers (Egger et al, 2022).…”
Section: Figure 1: Flow Chart Of Ghana Financial Incentives Trialsupporting
confidence: 88%
“…There is limited evidence regarding the unintended consequences of COVID-19 vaccine financial incentives. The most notable evidence to date are the results from U.S. and Swedish trials that found no evidence of significant negative unintended effects of financial incentives (Schneider et al, 2023). We explicitly design our Ghana trial in order to estimate geographic spillover effects of the cash incentive treatments that might result from diffusion of information about cash payments (Giné and Mansuri, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…Finding institutions that avoid or mitigate these kinds of objections may determine the extent to which societies succeed or fail in dealing with the challenges of our time. A stream of recent research at the design-behavior interface is thus concerned with understanding the empirical nature of such behavioral constraints (Ambuehl, 2017;Ambuehl, Bernheim, & Ockenfels, 2021;Berger, Ockenfels, & Zachmann, 2023;Kölle, Kübler, & Ockenfels, 2023;Leider & Roth, 2010;Schneider et al, 2023). Another literature develops mechanisms that are consistent with the constraints imposed by attitudes about appropriateness.…”
Section: Introductionmentioning
confidence: 99%
“…Or they might think the payments are compensation for something that isn't safe or could be unpleasant. Now, the results of two trials published in a paper on 11 January in Nature suggest that simple cash payments have no such unintended effects 4 . The research team took the important step of designing the studies to test a null hypothesis.…”
Section: Rigorously Designed Studies Can Dispel Suspicions That Offer...mentioning
confidence: 99%